Pharaohs, Freemasons and the discovery of the secret scrolls of Jesus. - Knight, Christopher (Arrow, 1997)
In this investigation into the origins of Freemasonry and the final resting place of the Dead Sea Scrolls, the authors, Knight and Lomas, come to some controversial conclusions.